Statistical analysis of socio-economic determinants on newborn birth weight in Nigeria - Ayenigba, Alfred Ayo; Afariogun, David Adebisi; Lawal, Sadia O. (Lithuanian Journal of Statistics, 2025)
This study identifies the main factors which were significantly associated with Low Birth Weight (LBW) as a socioeconomic condition. Using logistic regression, the variables that are statistically significant are antenatal, residence status, smoking status and sex. So, we conclude that there is a significant effect of socioeconomic factors in determining weight at birth in Nigeria and Cochran’s test reveals that the proportions at which socioeconomic factors affect weight at birth in Nigeria are statistically significantly different across the independent variables in the study.